Lei para todos : tensões trabalhistas entre “súditos do Eixo” e empregadores, durante a Segunda Guerra Mundial, em Pelotas - Soares, Tamires Xavier (2016)
This research aims to understand the labor tensions generated from the Second World War between immigrants “subjects of the Axis", employers and national workers in the city of Pelotas. For this we will use sources of labor proceedings of Justice of Pelotas and oral interviews with descendants of the workers involved in the actions. The research discusses how the war and class experiences have created labor tensions and the way that Labor Justice, the newly created dealt with equally new situations. Since the cases are heard amid the mobilization of war, in which labor laws are suspended and others are created. Thus, we focus our attention to examine the relationship between employer and foreign employees, domestic and foreign officials, the trial judges and the cunjuntura the moment, given by respondents.